REPRODUKSI IKAN ENDEMIK BUTINI (GLOSSOGOBIUS MATANENSIS WEBER 1913) BERDASARKAN KEDALAMAN DAN WAKTU DI DANAU TOWUTI, SULAWESI SELATAN - Mamangkey, Jefry Jack; Nasution, Syahroma Husni (Perhimpunan Biologi Indonesia, 2012)
Reproduction of Endemic Fish Butini (Glossogobius matanensis) Based on Depth and Time in Towuti Lake. Butini fish (Glossogobius matanensis) belonging to the Gobiidae family and is one ofendemic fish in Towuti Lake and classified as demersal fish. Fishing activities and habitat quality changes tend to reduce butini stocks in Towuti Lake. Therefore, it needs to be protected of stocksfor sustainability. This research is to determine reproduction of endemic fish based on depth and time as basic data for the effort of conservation and domestication. Gonad maturity that was analyzed histologically obtained five maturity stages. Based on the diversity of egg size, especially in the gonad maturity stage (IV), it is indicated that butini fish are classified as partial spawner. Male and female fish gonad mature (50%) at 36.22 and 31.43 cm total length, respectively. October and March, an estimated spawning peak of butini fish in Towuti Lake held this month at a depth of 150m and 200 m. Fecundity of butini fish in gonad maturity stage (III and IV) between 11184-66305 eggs and 14922-81522 eggs, respectively. The highest mean of fecundity there in October (56,907 eggs) and the lowest was found in July (25,447 eggs). Fecundity of fish at 25 m-200 m depths ranging from 30.778-35.329 eggs.Keywords: Reproduction, endemic fish, Glossogobius matanensis, depth and time, Towuti Lake